Interactions between EHD Proteins and Rab11-FIP2: A Role for EHD3 in Early Endosomal Transport - Naslavsky, Naava (The American Society for Cell Biology, 2006)
Eps15 homology domain (EHD) 1 enables membrane recycling by controlling the exit of internalized molecules from the endocytic recycling compartment (ERC) en route to the plasma membrane, similar to the role described for Rab11. However, no physical or functional connection between Rab11 and EHD-family proteins has been demonstrated yet, and the mode by which they coordinate their regulatory activity remains unknown. Here, we demonstrate that EHD1 and EHD3 (the closest EHD1 paralog), bind to the Rab11-effector Rab11-FIP2 via EH–NPF interactions. The EHD/Rab11-FIP2 associations are affected by the ability of the EHD proteins to bind nucleotides, and Rab11-FIP2 is recruited to EHD-containing membranes. These results are consistent with a coordinated role for EHD1 and Rab11-FIP2 in regulating exit from the ERC. However, because no function has been attributed to EHD3, the significance of its interaction with Rab11-FIP2 remained unclear. Surprisingly, loss of EHD3 expression prevented the delivery of internalized transferrin and early endosomal proteins to the ERC, an effect differing from that described upon EHD1 knockdown. Moreover, the subcellular localization of Rab11-FIP2 and endogenous Rab11 were altered upon EHD3 knockdown, with both proteins absent from the ERC and retained in the cell periphery. The results presented herein promote a coordinated role for EHD proteins and Rab11-FIP2 in mediating endocytic recycling and provide evidence for the function of EHD3 in early endosome to ERC transport.